Pengaruh Komunikasi Keluarga dan Disiplin Belajar Terhadap Prestasi Belajar Siswa Kelas V Sekolah Dasar - N Istiqlalia (Universitas Sebelas Maret, 2020)
The aim of this research is 1) To know the influence of family commucation to students' achievmen; 2) to know learning dicipline to students' achievment; 3) to know the influence of family communication and dicipline to students' achievement in the fifth grade. The kind of this research is quantitative research. the population is the fifth grade students in SD Negeri Sukorejo elementary school. The technique of collectig data is questionare and documentation. the instrument test is validity and realibility test. The result of this research is 1) family communication has possitif effect and significant to students achievment in SD Negeri Sukorejo elemntary school , suruh, semarang regency 2020/2021 academic year 2)learning dicipline haspossitif effect and significant to students achievment in SD Negeri Sukorejo elemntary school, suruh, semarang regency 2020/2021 academic year3) both of family communication and learning dicipline have influence to students achievement in gunungtumpeng elemntary school, suruh, semarang regency 2020/2021 academic year 4) communication variable gives 216% of the effectiveness, learning vriable gives 18,9% of the effectiveness. the amount of them is 40,5%, while 59,5% is residue that it influenced by the other variable.